Unveiling the Molecular Links Between Atrial Fibrillation and Atherosclerosis: Insights into Shared Pathogenesis and Ferroptosis Diagnostic Biomarkers - Xu B; Li H; Chen H; Teng D; Gong L; Zhong L; Yang J (Dove Medical Press, 2024)
Bowen Xu,1,2,* Hongye Li,1,2,* Hongping Chen,3 Da Teng,1,2 Lei Gong,2 Lin Zhong,2 Jun Yang2 1Qingdao Medical College of Qingdao University, Qingdao, Shandong, 266000, People's Republic of China; 2Department of Cardiology, Yantai Yuhuangding Hospital, Yantai, Shandong, 264000, People's Republic of China; 3Department of Cardiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, 221000, People's Republic of China*These authors contributed equally to this workCorrespondence: Lin Zhong; Jun Yang, Email linzhongyhd1971@sina.com; yangjyhd@hotmail.comObjective: Atherosclerosis(AS) is a vascular disease characterized by the development of plaque in the arteries, and atrial fibrillation (AF) is a common heart arrhythmia. These two conditions share several risk factors in common, such as aging, diabetes, obesity, and hypertension. Ferroptosis is a new mode of non-apoptotic cell death that plays a key role in cardiomyocyte death and has been associated with a variety of cardiac diseases. This study aimed to investigate the ferroptosis biomarkers and underlying biological mechanisms associated with AF and AS.Materials and Methods: The gene expression dataset was obtained from GEO database, differentially expressed genes (DEGs) and ferroptosis expressed genes (FDGs) were obtained by data processing and screening, and then functional enrichment, network construction, transcription factor prediction, identification of biomarkers by LASSO and SVM - RFE algorithms, and also immune infiltration analyses and cellular experiments were performed.Results: In AF and AS, 1627 and 571 DEGs were identified respectively, and 128 were intersected, and 47 common FDGs were also identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of DEGs revealed that they were associated with biological processes and pathways such as leukocyte immunity, and FDGs were also involved in specific functions and pathways. Fifteen key genes were identified, CSF1R and ITGAM expression differences were verified, and seven transcription factors were predicted to be differentially expressed. Characterized genes were screened to construct models with good diagnostic efficacy, and immune infiltration showed that NUPR1 was associated with altered immune environments, and WB indicated that NUPR1 was highly expressed in the disease model.Conclusion: Our study demonstrates that the ferroptosis gene NUPR1 plays a role in the pathogenesis of atrial fibrillation and atherosclerosis, and also provides valuable insights into their molecular mechanisms, which may contribute to the development of new targets and strategies for the treatment of these diseases.Keywords: atrial fibrillation, AF, atherosclerosis, AS, ferroptosis, CSF1R, ITGAM, NUPR1